1994
DOI: 10.1002/rcm.1290080913
|View full text |Cite
|
Sign up to set email alerts
|

Detection of 500‐nucleotide DNA by laser desorption mass spectrometry

Abstract: We report the first detection of DNA segments as large as 500 nucleotides by matrix-assisted laser desorption/ionization (MALDI) mass spectrometry, using picolinic acid and 3-hydroxypicolinic acid mixtures as desorption matrices. The successful detection of 500-nucleotide DNA indicates that laser mass spectrometry is now emerging as a new biotechnology tool for DNA-related research. It should be possible to utilize fast detection of large DNA segments by laser mass spectrometry for rapid human genome sequencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
62
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(62 citation statements)
references
References 17 publications
0
62
0
Order By: Relevance
“…On the other hand, mass spectrometry, especially matrix-assisted laser desorption/ionization (MALDI) time-offlight (TOF) mass spectrometry (MS) offers the advantage of separating a mixture of biomolecules in a fraction of milliseconds without gel electrophoresis and labeling (7)(8)(9)(10)(11)(12)(13)(14)(15). The detection range ofMALDI-TOFMS for DNA molecules has been extended to 500 bases long (16). These advances demonstrate that MALDI-TOFMS could offer considerable promise as a replacement for gel electrophoresis and labeling in DNA sequencing processes.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, mass spectrometry, especially matrix-assisted laser desorption/ionization (MALDI) time-offlight (TOF) mass spectrometry (MS) offers the advantage of separating a mixture of biomolecules in a fraction of milliseconds without gel electrophoresis and labeling (7)(8)(9)(10)(11)(12)(13)(14)(15). The detection range ofMALDI-TOFMS for DNA molecules has been extended to 500 bases long (16). These advances demonstrate that MALDI-TOFMS could offer considerable promise as a replacement for gel electrophoresis and labeling in DNA sequencing processes.…”
Section: Introductionmentioning
confidence: 99%
“…Since Matrix-Assisted Laser Desorption/ Ionization (MALDI) has been introduced, [3,4] much effort has been devoted to the development of oligonucleotide analysis by MALDI mass spectrometry. To date, Tang et al [5] and Liu et al [6] have reported the analysis of PCR products ϳ500 to 600 bases using UV-MALDI (at 337/355 nm), and Hillenkamp and co-workers extended the upper limit of DNA and RNA analyses up to ϳ2180 bases using IR-MALDI [7]. Applications such as analyzing short tandem repeats [8], gene-defect diseases [9 -11], and genotyping of single nucleotide polymorphisms [12] have been attempted.…”
mentioning
confidence: 99%
“…A large number of studies have been undertaken to better understand the fragmentation process [16 -34]. Generally, the severity of fragmentation is matrix-dependent, and a matrix of choice is 3-hydroxypicolinic acid (3-HPA) [35,36] (or the two component matrix-3HPA/picolinic acid [5]) because it results in a lesser amount of fragmentation and enables the analysis of larger oligonucleotides. The popular matrices for peptides and proteins, such as sinapinic acid (SA) instrument facility tend to produce significant fragmentation when used for oligonucleotide analysis.…”
mentioning
confidence: 99%
“…The introduction of ESI and MALDI made progressively larger nucleic acids accessible to MS analysis ( Figure 2) [25][26][27][28], which ushered in a period of rapid expansion into different areas of biomedical research. The challenges posed by the larger analytes were answered by the development of new strategies and experimental methods (reviewed in references [29 -33]), which sought to take full advantage of favorable characteristics exhibited by these ionization techniques, such as their intrinsic low-energy and ability to handle highly polar species.…”
Section: Making Headways In Biomedical Researchmentioning
confidence: 99%